Impact of ivermectin administered for scabies treatment on the prevalence of head lice in Atoifi, Solomon Islands. - Suny Coscione; Tommy Esau; Esau Kekeubata; Jason Diau; Rowena Asugeni; David MacLaren; Andrew C Steer; Christian Kositz; Michael Marks (Public Library of Science (PLoS), 2018)
BACKGROUND:Scabies and head lice are ubiquitous ectoparasitic infestations that are common across the Pacific Islands. Ivermectin is an effective treatment for both conditions, although the doses used vary. At a community level, mass drug administration (MDA) with ivermectin is an effective strategy to decrease prevalence of scabies. To what extent MDA with ivermectin will also reduce prevalence of head lice is unknown. METHODOLOGY:Head lice prevalence was assessed before and after MDA with oral ivermectin (at a dose of 200 micrograms per kilogram of body weight) administered on day 1 and day 8. The primary outcome was the change in prevalence of head louse infestation at two weeks compared to baseline. Longer term efficacy was assessed three months after MDA. RESULTS:118 participants were enrolled. Baseline prevalence of active head louse infestation was 25.4% (95% CI 18.4-34.0). At two-week follow-up, prevalence was 2.5% (95% CI 0.9-7.2), a relative reduction of 89.1% (95% CI 72.7-91.4%, p<0.001). At three-month follow-up, prevalence was 7.5% (95% CI 2.7-12.3), a relative reduction of 70.6% (95% CI 72.7%-91.4%, p <0.001). Head louse infestation was associated with younger age (age ≤10 years: prevalence 46.7%; adjusted odds ratio compared to adults of 7.2, 95%CI 2.0-25.9) and with having at least one other member of the household with active head louse infestation (adjusted odds ratio 4.3, 95%CI 1.7-11.1). CONCLUSIONS:Head louse infestation is common in the Solomon Islands. This proof of principle study shows that oral ivermectin at a dose of 200 micrograms per kilogram can reduce the burden of active head louse infestation, offering an additional collateral benefit of MDA with ivermectin for scabies control. TRIAL REGISTRATION:ClinicalTrials.gov NCT03236168.